Ecological Tourism Opportunities in the Area of Ognyanovo Dam - Savova, Adelina; Berberova, Ralitza (Annual of Natural Sciences Department, 2021)
The dam of Ognyanovo is located in the Eastern Sofia Plain, only 40 km away from the capital of Bulgaria. It is one of the country’s most beautiful places – full of biodiversity, especially as regards avifauna species. An important factor which makes the dam a special object of scientific and tourist interest is its location on one of the main bird migration routes: the Via Aristotelis. For three consecutive years, the area’s fauna potential has been studied and significant biodiversity has been identified. This study aims to explore the opportunities for ecotourism development there.